Hybrid Selective Harmonic Elimination PWM for Common-ModeVoltage Reduction in Three-Level Neutral-Point-ClampedInverters for Variable Speed Induction Drives (International Journal of Engineering and Computer Science, 2013)
This paper proposes a hybrid selective harmonic elimination pulsewidth modulation (SHEPWM) scheme for commonmode voltage reduction in three-level neutral-point-clamped inverter-based induction motor drives. The scheme uses the conventional SHEPWM (C-SHEPWM) to control the inverter at high frequency (≥ 0.9 motor rated frequency) and uses the modified SHEPWM (M-SHEPWM) to control the inverter at low frequency. It also uses a scheme to ensure the smooth transition between the two SHEPWM schemes. As a result, at high frequency, the C-SHEPWM provides the required high modulation index for the motor, while at low frequency, when a passive filter is less effective for common-mode voltage reduction, the MSHEPWM is used to suppress the common-mode voltage. Experimental results show that the proposed hybrid SHEPWM scheme could meet the modulation index need of the motor and reduce the common-mode voltage in the drive, and the two SHEPWM schemes could transition smoothly.